Treatment-Related Sexual Side Effects From the Perspective of Partners of Men With Prostate Cancer. Issue 5 (4th July 2019) - Grondhuis Palacios, Lorena A.; den Ouden, Marjolein E.M.; den Oudsten, Brenda L.; Putter, Hein; Pelger, Rob C.M.; Elzevier, Henk W.
Abstract: A cross-sectional survey was performed among partners and men who received treatment for prostate cancer to investigate whether demographic and clinical characteristics are associated with the extent of how difficult partners found it dealing with sexual side effects and the degree of having experienced sexual problems after treatment. Moreover, an aim was to determine whether sexual side effects have an impact on the relationship. A total of 171 partners were included. In all, 104 men (70.7%) experienced an increase in erectile complaints after treatment. Almost half of partners of men with an increase in erectile complaints (63.6%, n  = 63) found it difficult to deal with sexual side effects and 63.5% ( n  = 66) experienced sexual problems. Partners with lower education levels experienced fewer sexual problems than partners with higher education levels ( p  < .001). Furthermore, no significant associations were found on demographic characteristics, number of comorbidities, clinical characteristics (prostate-specific antigen level; tumor, node, and metastasis staging; Gleason grading), and type of treatment. The majority of men (58.4%, n  = 59) and partners (62.5%, n  = 65) indicated to not have experienced the impact of sexual side effects on their relationship.